Epigenomic and phenotypic characterization of DEGCAGS syndrome - Karimi, Karim; Weis, Denisa; Aukrust, Ingvild; Hsieh, Tzung Chien; Horackova, Marie; Paulsen, Julie; Mendoza Londono, Roberto; Dupuis, Lucie; Dickson, Megan; Lesman, Hellen; Lau, Tracy; Murphy, David; et al. (European Journal of Human Genetics, 2024)
Developmental Delay with Gastrointestinal, Cardiovascular, Genitourinary, and Skeletal Abnormalities syndrome (DEGCAGS, MIM #619488) is caused by biallelic, loss-of-function (LoF) ZNF699 variants, and is characterized by variable neurodevelopmental disability, discordant organ anomalies among full siblings and infant mortality. ZNF699 encodes a KRAB zinc finger protein of unknown function. We aimed to investigate the genotype-phenotype spectrum of DEGCAGS and the possibility of a diagnostic DNA methylation episignature, to facilitate the diagnosis of a highly variable condition lacking pathognomonic clinical findings. We collected data on 30 affected individuals (12 new). GestaltMatcher analyzed fifty-three facial photographs from five individuals. In nine individuals, methylation profiling of blood-DNA was performed, and a classification model was constructed to differentiate DEGCAGS from controls. We expand the ZNF699-related molecular spectrum and show that biallelic, LoF, ZNF699 variants cause unique clinical findings with age-related presentation and a similar facial gestalt. We also identified a robust episignature for DEGCAGS syndrome. DEGCAGS syndrome is a clinically variable recessive syndrome even among siblings with a distinct methylation episignature which can be used as a screening, diagnostic and classification tool for ZNF699 variants. Analysis of differentially methylated regions suggested an effect on genes potentially implicated in the syndrome’s pathogenesis.
CRIS-Team Scopus Importer:2024-11-01